2014
DOI: 10.1111/jnc.12768
|View full text |Cite
|
Sign up to set email alerts
|

Mu‐opioid receptor splice variants: sex‐dependent regulation by chronic morphine

Abstract: The gene encoding the mu-opioid receptor (MOR) generates a remarkable diversity of subtypes, the functional significance of which remains largely unknown. The structure of MOR could be a critical determinant of MOR functionality and its adaptations to chronic morphine exposure. Since MOR antinociception has sexually dimorphic dimensions, we determined the influence of sex, stage of estrus cycle and chronic systemic morphine on levels of MOR splice variant mRNA in rat spinal cord. Chronic systemic morphine infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 43 publications
5
35
1
Order By: Relevance
“…There is a growing literature indicating sex-specific expression patterns of opioid receptors as well as endogenous opioid expression, particularly in relation to the differential antinociception response between males and females (Gerald et al, 2008; Kren et al, 2008; Meyer et al, 2000; Wang et al, 2012). For example, it has been shown that there are sex-specific increases in mu opioid receptor expression within the spinal cord in male but not female rats (Verzillo et al, 2014) and the periaqueductal gray region (Loyd et al, 2008). In terms of changes observed in the accumbens, it has been shown that endogenous opioid gene expression is higher in females than males in the nucleus accumbens (Gugusheff et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing literature indicating sex-specific expression patterns of opioid receptors as well as endogenous opioid expression, particularly in relation to the differential antinociception response between males and females (Gerald et al, 2008; Kren et al, 2008; Meyer et al, 2000; Wang et al, 2012). For example, it has been shown that there are sex-specific increases in mu opioid receptor expression within the spinal cord in male but not female rats (Verzillo et al, 2014) and the periaqueductal gray region (Loyd et al, 2008). In terms of changes observed in the accumbens, it has been shown that endogenous opioid gene expression is higher in females than males in the nucleus accumbens (Gugusheff et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that sex differences in the effects of peripheral MOR agonists is partly mediated by sex differences in the changes of MOR expressions [34], tolerance/dependence results from different adaptational strategies (chronic systemic morphine influenced levels of MOR splice variant mRNA) in males and females [35], MOR expression in the PAG was sexually dimorphic contributed to the observed sex differences in morphine potency [36] and testosterone plays a key role in the regulation of MOR under inflammatory conditions and these differences in the antihyperalgesic effects of peripherally administered opioids are mediated by peripheral opioid receptor expression levels partially [37]. Thus, we determined to explore the different effects of μ opioid receptor agonists and aimed to investigate the mRNA expression of MOR variants of different brain regions by SYBR green quantitative PCR (qPCR) in male and female mice and prepared to figure out some certain relationships between MOR variants and these sex-associated reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple physiological and environmental stimuli are known to alter constitutive and alternative splicing. Accordingly, chronic use and abuse of opioids, such as methadone and morphine, has been found to alter splicing patterns of the MOR (Vousooghi et al, ; Verzillo et al, ; Xu et al, ). The current study confirms and expands upon these previous findings, as our results demonstrate that morphine treatment significantly increases MOR‐1X mRNA expression in a human cell‐line model of dopaminergic neurons (Fig.…”
Section: Discussionmentioning
confidence: 99%